Popper's experiment with randomly paired photons in thermal state. (15th January 2015) - Peng, Tao; Simon, Jason; Chen, Hui; French, Robert; Shih, Yanhua
Abstract: We realized Popper's thought experiment via the photon number fluctuation correlation measurement of random paired photons in thermal state. The experiment produces the same results as that of Kim and Shih in 1998 with entangled photon pairs, which agreed with Popper's prediction. Although the observation cannot be considered as a violation of the uncertainty relation as Popper believed, this experiment reveals a concern about nonlocal interference of a random photon pair, which involves the superposition of multi-photon amplitudes, and multi-photon detection events at a distance.